Evaluating teamwork development in combat training settings: an exploratory case study utilising the Junior Leaders’ Field Gun competition - Smy, Victoria; Cahillane, Marie; MacLean, Piers; Hilton, Mike; Humphreys, Lisa (Elsevier, 2021)
A behaviourally-anchored observational rating scale (BAORS) of teamwork based upon the ‘Big Five’ teamwork model (Salas et al., 2005) was selected and adapted for use in a combat training setting – a UK military field gun competition. The teamwork development of 16 newly-formed teams training to master a historic tactical drill was evaluated over the course of a week-long residential programme. Training culminated in a timed field gun competition. Teams were trained and mentored in respects to teamwork and taskwork by experienced military instructors. Teamwork was assessed at the outset and end of training. Significant improvements were evident on all teamwork process dimensions, with the greatest improvement seen in teams’ shared understanding of teamwork roles and strategies (shared mental models). The lack of an association between teamwork development and final drill performance is explored, as is the utility of the measurement protocol developed for teamwork assessment in other settings
Keywords: Military field gun combat exercise; Teamwork training; Applied teamwork measurement